Anti-Inflammatory Effect Of Extract And Fractions Of Gaharu (Aquilaria malaccensis Lamk.) Leaves - Nur Hidayah; Ritbey Ruga; Chairul Saleh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Anti-inflammatory activity test of extract and fraction of gaharu leaf (Aquilaria malaccensis Lamk.) against protein denaturation inhibition in vitro has been carried out. This study aims to determine the percent inhibition of protein denaturation and the strength of anti-inflammatory activity of the concentrated methanol extract, ethyl acetate fraction, and methanol-water fraction of gaharu leaves (Aquilaria malaccensis Lamk.). BSA (Bovine serum albumin) is used as the protein to be heated. Diclofenac sodium was used as the positive control, and the negative control used the appropriate solvent. Based on phytochemical screening tests, methanol extracts are known to contain secondary metabolites, including flavonoids, triterpenoids, steroids, and phenolics. The n-hexane fraction contains triterpenoid and steroid compounds. The ethyl acetate fraction contains flavonoid, triterpenoid, steroid, and phenolic compounds, while the methanol-water fraction contains flavonoid, triterpenoid and phenolic compounds. The results of the anti-inflammatory activity test of crude extract methanol and ethyl acetate fraction showed moderate antiinflammatory potential with IC50 values of 181.58- 168.87 ppm, respectively, while the methanol-water fraction has strong anti-inflammatory potential with IC50 value of 60.84 ppm.